2019
DOI: 10.1021/acs.est.9b05856
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Generation of Singlet Oxygen in the Metal-Free Peroxymonosulfate Activation Process: Important Role of Electron-Deficient Carbon Atoms

Abstract: A nonradical oxidation process via metal-free peroxymonosulfate (PMS) activation has recently attracted considerable attention for organic pollutant degradation; however, the origin of singlet oxygen ( 1 O 2 ) generation still remains controversial. In this study, nitrogen-doped carbon nanosheets (NCN-900) derived from graphitic carbon nitride were developed for activation of PMS and elucidation of 1 O 2 production. With a large specific surface area (1218.7 m 2 g −1 ) and high nitrogen content (14.5 at %), NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
138
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(165 citation statements)
references
References 39 publications
(76 reference statements)
6
138
1
Order By: Relevance
“…S26 A ). This contradicts the previous findings that D 2 O is a promoter for singlet oxygenation because the lifetime of 1 O 2 in D 2 O is extended up to 10 times ( 47 , 48 ). Thus, 1 O 2 was not primarily responsible for BPA degradation under such conditions, indicating the existence of a secondary nonradical PMS activation pathway ( 49 , 50 ).…”
Section: Resultscontrasting
confidence: 96%
“…S26 A ). This contradicts the previous findings that D 2 O is a promoter for singlet oxygenation because the lifetime of 1 O 2 in D 2 O is extended up to 10 times ( 47 , 48 ). Thus, 1 O 2 was not primarily responsible for BPA degradation under such conditions, indicating the existence of a secondary nonradical PMS activation pathway ( 49 , 50 ).…”
Section: Resultscontrasting
confidence: 96%
“…[7c] It is difficult to completely eliminate the effect of the simultaneous production of strong oxidizing COH which would mask and complicate the transformation. [9] Furthermore, the effect of carbon substrate on the Co-N active site is often overlooked. Graphene, [10a] carbon nanotubes, [10b] metal-organic frameworks (MOF), [10c] and carbon nitride [10d] have been widely employed as supporting catalysts, which play an important role in manipulating the electronic structure of the active sites and hence interactions with reactant.…”
mentioning
confidence: 99%
“…21,159 1 O 2 -Dominated oxidation processes were also reported in carbon/PS catalytic systems. 108,160–169 Yu and co-authors reported the 1 O 2 -dominated degradation process in the sludge-derived carbon/PMS catalytic system that showed excellent performance for BPA degradation. 123 It was found that the ketone structure in the carbon was the main active site for the formation of 1 O 2 , the reaction route of which is different from the above-mentioned O 2 ˙ − route (Fig.…”
Section: Effects Of Anions On Persulfate-based Aops For Sow Treatmentmentioning
confidence: 99%
“…Besides the ketone structure, carbon defects and electronegative N doping were also suggested as the active sites for activating PS to produce 1 O 2 . 161,170 However, the detailed catalytic mechanisms are still unclear. Recently, Luo and co-authors have found that the N-doped graphitic carbon/PMS system showed a 1 O 2 -dominated pathway for efficient BPA degradation.…”
Section: Effects Of Anions On Persulfate-based Aops For Sow Treatmentmentioning
confidence: 99%